2021
DOI: 10.1177/1557085120987632
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods and Intimate Partner Violence: A Decade in Review

Abstract: We consider the broad developments that have occurred over the past decade regarding our knowledge of how neighborhood context impacts intimate partner violence (IPV). Research has broadened the concept of “context” beyond structural features such as economic disadvantage, and extended into relationships among residents, collective “action” behaviors among residents, cultural and gender norms. Additionally, scholars have considered how the built environment might foster (or regulate) IPV. We now know more abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…13,[20][21][22][23][24][25][26][27][28] In contrast, empirical evidence for the presumed effect of residential instability on IPV is scarce. 9,10 Some studies reported nonsignificant associations 13,[28][29][30] while others observed negative associations, in contradiction with the SDT. 20,[23][24][25] The role of ethnocultural heterogeneity is also equivocal.…”
Section: Social Disorganization Theory and Intimate Partner Violencementioning
confidence: 98%
See 1 more Smart Citation
“…13,[20][21][22][23][24][25][26][27][28] In contrast, empirical evidence for the presumed effect of residential instability on IPV is scarce. 9,10 Some studies reported nonsignificant associations 13,[28][29][30] while others observed negative associations, in contradiction with the SDT. 20,[23][24][25] The role of ethnocultural heterogeneity is also equivocal.…”
Section: Social Disorganization Theory and Intimate Partner Violencementioning
confidence: 98%
“…However, a growing number of studies, mostly conducted in the U.S, have analysed neighbourhood-level factors in relation to IPV, and recent literature reviews suggest that different neighbourhood characteristics are associated with IPV. 8 11 In these studies, the influence of local environments (i.e., neighbourhoods) on IPV the social disorganization theory (SDT) 12 is the conceptual framework most frequently referred to. 8 , 9 This theory posits that neighbourhood sociodemographic characteristics, specifically socioeconomic status (SES), single parenthood, residential instability and ethnocultural heterogeneity, are associated with crime and violence.…”
Section: Introductionmentioning
confidence: 99%
“…Further to this, the specter and spectrum of gendered violence shape the everyday realities of women, which in turn could influence their perceived ability to control their own victimization (Jackson 2016; Walklate 2017). As victimization against women clusters within particular neighborhoods (Beyer, Wallis, and Hamberger 2015; Wright, Pimchevsky, and Xie 2021), there are likely ecological cues of vulnerability that specifically shape women's perceived control over their victimization.…”
Section: The Neighborhood Context and Perceptions Of Control Over Vic...mentioning
confidence: 99%
“…There has been a growth in literature examining factors related to IPV and explaining such behavior within contemporary theoretical frameworks (Hayes, 2021 ; Voith, 2019 ; Wright et al, 2021 ). Despite this, extant frameworks employed in understanding IPV have been shown to be of limited applicability and/or need to be theoretically re-conceptualized among non-US samples (Hayes et al, 2021 ; VanderEnde et al, 2012 ).…”
Section: India and Ipvmentioning
confidence: 99%